On the issue of secular trends in modern anthropology - A. A. Gaivoronsky; A. A. Semenov; V. V. Chrishtop; G. I. Nichiporuk; O. A. Osipov; R. I. Glushakov (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье, 2025)
Long-term trends are classically represented by the dynamics of body length and weight. However, in order  to  solve  practical  problems associated with the development of a regulatory framework regulating the “man-machine" system, the production of clothing and personal protective equipment, including for military activities, it is necessary to create a holistic picture of the changes.Purpose: to systematize data on long-term trends in morphofunctional indicators of practically healthy individuals in combination with data from anthropometric studies. The selection of literary sources over the past 20 years was carried out in the E-library, Pubmed and Scopus databases. The exclusion criterion was the age of subjects under 16 years. The main long-term changes are associated with an increase in body mass index due to body weight, against the background of stagnation in its length. Changes in the last two decades include developmental retardation, debrachycephalization and leptoprosopia, changes in body shape, sex inversion, decreased aerobic tolerance, decreased agility, decreased certain blood biochemical parameters, cellularity of body fluids and cognitive abilities, as well as increased activity of the sympathetic nervous system. Thus, it can be stated that a wide range of organs are involved in secular trends, which requires targeted research from the standpoint of systemic anatomy.